Game-Based Learning Models And Improving Student Learning Outcomes In History Subjects - Rahmawati, Vini; Umamah, Nurul; Sumardi, Sumardi; Murtinah, Murtinah (JURNAL HISTORICA, 2022)
This study aims to examine the effect of the application of the game-based learning model on student learning outcomes in historical subjects. This study uses a quantitative approach with the type of experimental research. The research design uses a quasi-experimental model pretest-posttest,, also a non-equivalent control-group design. The sample consists of 66 students in classes XI IPS 4 and XI IPS 1 at SMA Negeri 1 Gambiran. Collect the data using documentation and tests. The data analysis technique uses the one-way ANOVA test and the LSD (Least Significant Different) advanced test software assisted by SPSS 22 for Windows. The results of data analysis show that, there is an effect of the application of the game-based learning model on student learning outcomes in historical subjects. The results of the one-way ANOVA test show that the probability value (sig.) in the experimental group is 0,000<0,05, with the LSD (Least Significant Different) further test of 11.57576. And ANOVA test shows that the probability value (sig.) in the control group is 0,000<0,05, with the LSD (Least Significant Different) further test of 7.48485. Therefore, there is an effect of student learning outcomes in the experimental group that taught using a game-based learning model. Keywords: Learning 4.0, game-based learning, student learning outcomes